2016
DOI: 10.2174/1874350101609010095
|View full text |Cite
|
Sign up to set email alerts
|

The Language of Memory: Narrating Memories of Parents and Friends

Abstract: Abstract:The purpose of this study was to compare narrated memories of parents and friends, recounted by both males and females. A total of 177 Italian undergraduates were asked to recall and to write in detail one relevant memory regarding their relationship with either parents or friends during adolescence. Half of the participants wrote a narrative about parents and half about friends. Narratives were examined using both a content and a lexical linguistic method of analysis.The results showed that the langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
1
2
1
Order By: Relevance
“…This is partly because adolescents strive for emancipation from parents in order to establish social autonomy and their own personal identity (Laursen, Coy, & Collins, ). In contrast to other findings (Peterson et al, ; Smorti et al, ), we found females in the younger subsample spoke more negatively about their parents than males. Although daughters tend to have closer and warmer relationships with their parents than sons (Fingerman, ), the greater negativity of their parent‐related narratives might reflect their tendency to be more elaborate when depicting internal states (Fivush, Bohanek, Zaman, & Grapin, ; Fivush & Buckner, ; Grysman, ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is partly because adolescents strive for emancipation from parents in order to establish social autonomy and their own personal identity (Laursen, Coy, & Collins, ). In contrast to other findings (Peterson et al, ; Smorti et al, ), we found females in the younger subsample spoke more negatively about their parents than males. Although daughters tend to have closer and warmer relationships with their parents than sons (Fingerman, ), the greater negativity of their parent‐related narratives might reflect their tendency to be more elaborate when depicting internal states (Fivush, Bohanek, Zaman, & Grapin, ; Fivush & Buckner, ; Grysman, ).…”
Section: Discussioncontrasting
confidence: 99%
“…While parents remain important in people's life stories, the view on them changes with age. In congruence with other developmental findings (Larson, Richards, Moneta, Holmbeck, & Duckett, ; Smetana, Campione‐Barr, & Metzger, ; Smorti et al, ), we found an increase of negative evaluations of the parental relationship especially throughout adolescence. This is partly because adolescents strive for emancipation from parents in order to establish social autonomy and their own personal identity (Laursen, Coy, & Collins, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Memory has traditionally been one of the central concepts in philosophy and psychology, but recent decades have seen its persistent penetration into other research fields (see Assmann, 2008;Erll, 2011;Halbwachs, 1997;Hirsch, 2008;Klein, 2000), linguistics being no exception (see Bragina, 2007;Chafe, 1973;Gasparov, 2010;Smorti, Peterson & Tani, 2016;Wierzbicka, 2007). Theories and models describing memorylanguage relationships vary significantly across fields and authors.…”
mentioning
confidence: 99%